The Effect of Smart University Characteristic on Entrepreneurial Orientation of Students: The Mediating Role of Knowledge Sharing - Swadi A.F.; Al-Dalaien A.A.A.-H. (World Scientific and Engineering Academy and Society, 2023)
Smart university is a new concept in education. The characteristic and impact of this university on creating entrepreneurial oriented community has not received adequate attention in the context of developing countries. The purpose of this study is to examine the effect of smart university characteristics (course quality, staff capability, and infrastructure) on entrepreneurial orientation (EO). Knowledge sharing between industry and university is proposed as a mediator. This study is a quantitative and it collects the data using a questionnaire. The data collection took place between April 2020 to August 2020. The data was collected from 279 master of business administration (MBA) graduates and students in Iraq. The data analysis was conducted using smart partial least square (Smart PLS). The findings showed that the effect of smart university characteristics are significant. In addition, knowledge sharing mediated the effect of the characteristics, except infrastructure, on EO. More attention has to be paid to the employment of skilful staff and to focus on the relationship between university and industry. 2022, World Scientific and Engineering Academy and Society. All rights reserved.